Distribution, relative abundance, and developmental morphology of paralarval cephalopods in the western North Atlantic Ocean - Vecchione, Michael; United States. National Marine Fisheries Service (Seattle, Wash. : U.S. Dept. of Commerce, [National Oceanic and Atmospheric Administration, National Marine Fisheries Service, 2001)
Mode of access: Internet.